On the interpretation of in situ HONO observations via photochemical steady state. (22nd April 2016) - Crilley, Leigh R.; Kramer, Louisa; Pope, Francis D.; Whalley, Lisa K.; Cryer, Danny R.; Heard, Dwayne E.; Lee, James D.; Reed, Christopher; Bloss, William J.
Abstract : A substantial body of recent literature has shown that boundary layer HONO levels are higher than can be explained by simple, established gas-phase chemistry, to an extent that implies that additional HONO sources represent a major, or the dominant, precursor to OH radicals in such environments. This conclusion may be reached by analysis of point observations of (for example) OH, NO and HONO, alongside photochemical parameters; however both NO and HONO have non-negligible atmospheric lifetimes, so these approaches may be problematic if substantial spatial heterogeneity exists. We report a new dataset of HONO, NO x and HO x observations recorded at an urban background location, which support the existence of additional HONO sources as determined elsewhere. We qualitatively evaluate the possible impacts of local heterogeneity using a series of idealised numerical model simulations, building upon the work of Lee et al. ( J. Geophys. Res., 2013, DOI: 10.1002/2013JD020341). The simulations illustrate the time required for photostationary state approaches to yield accurate results following substantial perturbations in the HO x /NO x /NO y chemistry, and the scope for bias to an inferred HONO source from NO x and VOC emissions in either a positive or negative sense, depending upon the air mass age following emission. To assess the extent to which these impacts may be present in actual measurements, we present exploratory spatially resolved measurements of HONO and NO x abundance obtained using a mobile instrumented laboratory. Measurements of the spatial variability of HONO in urban, suburban and rural environments show pronounced changes in abundance are found in proximity to major roads within urban areas, indicating that photo-stationary steady state (PSS) analyses in such areas are likely to be problematic. The measurements also show areas of very homogeneous HONO and NO x abundance in rural, and some suburban, regions, where the PSS approach is likely to be valid. Implications for future exploration of HONO production mechanisms are discussed.